Wartość i jakość w usługach - Barbara Iwankiewicz-Rak (Ekonomiczne Problemy Usług, 2018)
Value for the customer, co-creation of value in services is a contemporary challenge for marketing activities of service providers. At the same time, the external focus of customer satisfaction is quality management in services and adapting quality management systems. Creating value for customer and service quality management represent a common decision-making process for the customer and the service provider. The Quality Function Development (QFD) model, which integrates the Kano and Servqual models together with the “Quality House” diagram, is an example of the co-creating value for consumer and quality and value of a product / service offering.